Needs analysis of communication strategies in the Project-Based Learning Model - Fauziya, Diena San; Fuadin, Ahmad; Permana, Indra (Journal of Applied Studies in Language, 2025)
This study analyzes the need for communication strategies in the Project-Based Learning (PjBL) model. As a transformative educational approach, PjBL emphasizes 21st-century skills, with communication playing a central role in ensuring effective collaboration and learning outcomes. Although PjBL encourages interaction and teamwork, significant communication challenges persist in its implementation, particularly in higher education settings. This research employs a mixed-methods approach with a parallel convergent design, integrating qualitative and quantitative data simultaneously. The study involved two universities in West Java, with data collected through interviews, surveys, and literature review. The findings reveal three essential communication strategies that are needed to support the implementation of the Project-Based Learning (PjBL) model effectively: (1) strategic use of technology as a communication medium, (2) regulated frequency of interaction to maintain group coherence, and (3) multimodal forms of communication, including verbal, nonverbal, and digital, tailored to project needs. These strategies are instrumental in enhancing collaboration, clarity, and efficiency throughout the project process. Results show that 35% of students have adequate digital literacy, 40% face difficulties using digital tools, and 25% express the need for additional training to improve their communication skills on digital platforms. Additionally, structured and scheduled communication significantly enhances group collaboration. This study highlights the importance of developing communication strategies that include digital literacy training and the optimal use of technology to support effective communication in PjBL. These findings provide a foundational insight for future research and policy development aimed at integrating targeted communication frameworks into innovative, student-centered pedagogies.